Iron‐Based Electrodes Meet Water‐Based Preparation, Fluorine‐Free Electrolyte and Binder: A Chance for More Sustainable Lithium‐Ion Batteries?. Issue 11 (5th May 2017) - Valvo, Mario; Liivat, Anti; Eriksson, Henrik; Tai, Cheuk‐Wai; Edström, Kristina
Abstract: Environmentally friendly and cost‐effective Li‐ion cells are fabricated with abundant, non‐toxic LiFePO4 cathodes and iron oxide anodes. A water‐soluble alginate binder is used to coat both electrodes to reduce the environmental footprint. The critical reactivity of LiPF6 ‐based electrolytes toward possible traces of H2 O in water‐processed electrodes is overcome by using a lithium bis(oxalato)borate (LiBOB) salt. The absence of fluorine in the electrolyte and binder is a cornerstone for improved cell chemistry and results in stable battery operation. A dedicated approach to exploit conversion‐type anodes more effectively is also disclosed. The issue of large voltage hysteresis upon conversion/de‐conversion is circumvented by operating iron oxide in a deeply lithiated Fe/Li2 O form. Li‐ion cells with energy efficiencies of up to 92 % are demonstrated if LiFePO4 is cycled versus such anodes prepared through a pre‐lithiation procedure. These cells show an average energy efficiency of approximately 90.66 % and a mean Coulombic efficiency of approximately 99.65 % over 320 cycles at current densities of 0.1, 0.2 and 0.3 mA cm −2 . They retain nearly 100 % of their initial discharge capacity and provide an unmatched operation potential of approximately 2.85 V for this combination of active materials. No occurrence of Li plating was detected in three‐electrode cells at charging rates of approximately 5C. Excellent rate capabilities of up to approximately 30C are achieved thanks to the exploitation of size effects from the small Fe nanoparticles and their reactive boundaries. Abstract : BOB's your uncle : Environmentally friendly and cost‐effective Li‐ion cells are fabricated with abundant, nontoxic LiFePO4 cathodes and iron oxide anodes. This electrochemical system relies on a nanostructured iron oxide in a deeply lithiated Fe/Li2 O state as an anode in combination with an entirely fluorine‐free binder (sodium alginate) and an electrolyte salt [lithium bis(oxalato)borate (LiBOB)] coupled to the LiFePO4 cathode.